THE JOB GUARANTEE: FULL EMPLOYMENT, PRICE STABILITY AND SOCIAL PROGRESS - EHNTS, DIRK H.; HÖFGEN, MAURICE (Society Register, 2019)
This paper presents the idea of the Job Guarantee (JG), which is a logical extension of the paradigm of a tax-driven fiat currency. The JG involves the government offering a public purpose-oriented job with a fixed hourly wage and job benefits to anyone willing to work. The JG as a bottom-up approach is locally administered but federally funded. As the analytical lens of MMT reveals, a monetarily sovereign government is always able to provide the spending required. Macroeconomically, the JG works as an automatic countercyclical stabilizer and an excellent tool for aggregated demand management, ensuring the economy is continuously operating at full capacity. On top, the JG uses an employed buffer stock approach as a superior means to maintain price stability. Next to its favourable macroeconomic impacts, the JG offers many social benefits, particularly related to continuous employment, working conditions in the private sector, power relations in the labour market and democracy. While the JG and Universal Basic Income (UBI) are often discussed as comparable, competing policy proposals, the JG addresses more macroeconomic and social issues than the UBI does. This paper concludes that the JG qualifies for being the single most effective policy in order to drive the economy towards continuous full employment and price stability while realizing additional social benefits.